FIRE EXTINGUISHING METHODS - S. M Umarova , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In preventing the development of fire, it is important not only to reduce its speed, but also to choose firefighting methods and means. To reduce the combustion process, it is necessary to reduce the content of combustible parts, reduce the oxidizing agent (air oxygen), reduce the temperature of the process, or increase the energy against the combustion reaction.